Synthesis and Characteristics of Calcium Phosphate from White Mussel Shell - Srie Muljani; Ketut Sumada; Nove Kartika (Future Science)
Biomaterials are materials that have been developed for repair, recovery of function, and replacement of diseased or damaged parts of the body especially in cases of fractures. The material for biomaterial that is commonly used is calcium phosphate (Ca3(PO4)2). The purpose of this research is to synthesize calcium phosphate and study its characteristics. The source of calcium carbonate in this study was from white mussel shells. The experiment was carried out by reacting calcium carbonate (CaCO3) and phosphoric acid (H3PO4) to form the liquid phase of calcium phosphate. The calcium phosphate solution was filtered and the filtrate obtained was added with a solution of NaOH as a pH controller, stirred using a magnetic stirrer in the time range from 10 to 50 minutes to form a calcium phosphate crystal. Filtration is carried out to separate the calcium phosphate crystals from the solution. The results showed calcium phosphate products containing 62% of ?-dicalcium phosphate (?-Ca2P2O7) and 38% of hydroxyapatite (Ca10(PO4)6(OH)2) so that it could be stated that the product was biphasic calcium phosphate. The raw material of white mussel shell powder was analyzed using X-Ray Fluorescence (XRF), while the calcium phosphate solution was analyzed by Spectrophotometry, Gravimetry, and AAS (calcium test). Hydroxyapatite products were analyzed by XRF, XRD (X-Ray Diffraction), FTIR (Fourier Transform InfraRed), and SEM (Scanning Electron Microscopy).